Pedal trajectory alters maximal single-leg cycling power - Martin, J. C.; Lamb, S. M.; Brown, N. A. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: Muscular power produced during in vitro cyclic contraction has been reported to vary with muscle-length trajectory. The purpose of this study was to determine whether maximal human single-leg cycling power could be similarly altered by manipulating pedal trajectory. METHOD: Seven trained cyclists performed maximal single-leg cycle ergometry. Pedal trajectory was manipulated by repositioning the ergometer drive sprocket off-center with respect to the crank axle, such that the leg-extension phase occupied 42, 50, or 58% of the cycle time (LEP42, LEP50, and LEP58, respectively). RESULTS: Maximum instantaneous power was 12% greater for LEP58 (1984 +/- 143 W) than LEP50 (1838 +/- 126 W), which was 8% greater than that for LEP42 (1645 +/- 112 W). Maximum power, averaged over a complete revolution of the crank, was 4% greater for LEP58 (636 +/- 59 W) than for LEP50 (613 +/- 53 W), which was 18% greater than that for LEP42 (520 +/- 43 W). CONCLUSIONS: These findings, paralleling those for an in vitro model, confirmed our hypothesis that maximal single-leg cycling power could be altered by manipulating pedal trajectory. Alterations in power were likely due to concomitant effects of muscle-shortening velocity, muscle excitation, and biomechanical constraints. Additional research is needed to determine whether greater leg-extension phase ratios can elicit further increases in power and whether similar results can be obtained during bilateral cycling.